TINU-associated Fanconi syndrome: a case report and review of literature - Bernard Vô; Jean Cyr Yombi; Selda Aydin; Nathalie Demoulin; Halil Yildiz (BMC Nephrology, 2018)
Abstract Background Tubulo-interstitial Nephritis and Uveitis (TINU) syndrome is a rare oculo-renal inflammatory disease. Renal tubular defects are usually found, but full proximal tubular abnormalities have rarely been described. Case presentation We report the case of a 55-year old woman, native from Morocco, presenting with bilateral, non-granulomatous, anterior uveitis, mild renal insufficiency, leucocyturia and glycosuria. Further work-up showed hypophosphatemia and hyperphosphaturia, hypouricemia and hyperuricosuria, and hyper aminoaciduria, consistent with Fanconi syndrome. A kidney biopsy was obtained and showed diffuse interstitial infiltrates with tubular necrosis. The patient improved after the initiation of a corticosteroid therapy, with tapering dose. Conclusions We reviewed the literature and found nine similar cases. This association mostly occurs in adult woman, without current evidence for an ethnic predilection, unlike previously reported. The renal prognosis seems favorable after corticosteroid therapy, even in case of severe renal injury. Nonetheless mild tubular defects may persist after treatment or spontaneous remission.